Perception of family functionality during social confinement by Coronavirus Disease 2019 / Percepção da funcionalidade familiar durante o confinamento social devido ao Coronavírus 2019 - Fernandes, Carla Sílvia; Magalhães, Bruno; Silva, Sílvia; Edra, Beatriz (Journal of Nursing and Health, 2020)
Objective: to assess the perception of family functionality in times of social confinement by Coronavirus 2019 pandemic. Method: it's a descriptive, correlational and cross-sectional study with Portuguese population regarding sociodemographic characteristics, vital cycle phase and application of the Family Assessment Scale Adaptation, Partnership, Growth, Affection and Resolve. Results: the sample consisted of 376 people. The Scale average score is 8.18. Despite the average value indicates a highly functional family, 18.9% of the participants’ present values below, compatible with a family with moderate dysfunction or with severe dysfunction. Conclusions: the pandemic can stimulate awareness about the important role of the family in people's lives and nurses to think of the family as the focus of care and their intervention.